2006
DOI: 10.1038/sj.ijo.0803342
|View full text |Cite
|
Sign up to set email alerts
|

Influence of obesity on accurate and rapid arm movement performed from a standing posture

Abstract: Introduction: Obesity yields a decreased postural stability. The potentially negative impact of obesity on the control of upper limb movements, however, has not been documented. This study sought to examine if obesity imposes an additional balance control constraint limiting the speed and accuracy with which an upper limb goal-directed movement performed from an upright standing position can be executed. Method: Eight healthy lean subjects (body mass index (BMI) between 20.9 and 25.0 kg/m 2 ) and nine healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
1
20

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 32 publications
8
63
1
20
Order By: Relevance
“…Additionally, physical movements by obese men may be less efficient leading to such individuals being at higher risk of injuries than those with normal weight in a large number of work tasks and daily activities 28) . Previous studies reported that weight loss improves balance control in obese subjects and the extent of the improvement was directly related to the amount of weight loss 29,30) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, physical movements by obese men may be less efficient leading to such individuals being at higher risk of injuries than those with normal weight in a large number of work tasks and daily activities 28) . Previous studies reported that weight loss improves balance control in obese subjects and the extent of the improvement was directly related to the amount of weight loss 29,30) .…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies investigated the effect of obesity on gross motor skills such as walking backwards along balance beams of decreasing width, moving sideways on wooden boards, one-legged hopping over a foam obstacle, and two-legged jumping from side to side [12,13], or on fine motor skills such as a peg placing task [6]. However, the relationship between obesity and the execution of motor tasks challenging the movement control at different difficulty levels realized in different postural context have not been closely documented among children, although it has been in adults [1,2]. Obesity adds a balance control constraint, however, movement time would be longer when the aiming requires more precision in standing and seated position for children, explaining the results previously observed for a functional task [12,13].…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies showed that obesity was linked with a reduced efficiency of mechanisms responsible for postural and movement control in standing position among adults [1][2][3][4]. For instance, reduced postural stability while standing leads to longer movement time and deceleration phase during a goal-directed movement in obese [2].…”
Section: Introductionmentioning
confidence: 98%
“…There are also many other possible associations between fat mass and bone mass on the molecular and cell level, including adipocyte hormones, estrogens, leptin, IL-6 and insulin [16,17]. In addition to any effects relating to bone mass, obesity has been postulated to increase the risk of falling [18], as it has been shown to increase postural instability [19,20] and decrease accuracy when performing rapid movements [19].…”
Section: Introductionmentioning
confidence: 99%